Plasma Exosomal MiRNAs Expression Profile in Mesial Temporal Lobe Epilepsy With Hippocampal Sclerosis: Case-Control Study and Analysis of Potential Functions - Huang, Li-Gang; Luo, Yun-He; Xu, Ji-Wen; Lu, Qin-Chi (Frontiers in Molecular Neuroscience, 2020)
Background: To explore an expression profile in plasma exosomal miRNAs of mesial temporal lobe epilepsy with hippocampal sclerosis (mTLE+HS) patients and investigate the associated clinical significance and putative pathways involved. Methods: Plasma exosomal miRNAs were measured in 6 mTLE+HS patients who were confirmed with pre-surgical stereo-electroencephalography and 6 without hippocampal sclerosis (mTLE-HS) using Illumina HiSeq 2500. Then 6 dysregulated miRNAs were chosen for validation in an independent sample of 18 mTLE+HS patients and 18 mTLE-HS controls using RT-qPCR. Receiver operating characteristic curve was conducted to evaluate the diagnostic value of miRNAs in HS. Bioinformatic analyses were conducted to reveal in which pathways these miRNAs were involved. Results: We revealed that a total of 42 exosomal miRNAs were differentially expressed in mTLE+HS. Among them, 25 were increased and 17 decreased. After validation, hsa-miR-129-5p, -214-3p, -219a-5p, and -34c-5p were confirmed as being upregulated, while hsa-miR-421 and -184 were significantly downregulated in mTLE+HS. Moreover, hsa-miR-184 had the best diagnostic value for discriminating mTLE+HS with 88.9% sensitivity and 83.3% specificity. These 6 miRNAs regulated several genes from neurotrophin-, hippo-, p53-, TGF-beta-, HIF-1-, mTOR-related pathways. Conclusions: Six miRNAs were dysregulated in mTLE+HS patients and targeted several genes. This result might facilitate pathological mechanistic studies of miRNAs in HS and represent potential diagnostic biomarkers. These provided the rationale for further confirmation studies in larger cohorts of prospective patients.